Reinforced composite as a feeder for 3D printing application - Nisa Naima Khalid; Nabilah Afiqah Mohd Radzuan; Abu Bakar Sulong; Farhana Mohd Foudzi; Mohd Zamzuri Ahmad Shukri (Penerbit Universiti Kebangsaan Malaysia, 2022)
Kenaf fibre has a low environmental impact because it is recyclable, light density and strong to be used as a product. Natural fibres, especially kenaf fibre, are undertilised and understudied in 3D printing technology. 3D technology is gaining traction to replace traditional methods because it saves cost and production time. This study focuses on producing kenaf composite materials that can be used as a feeder for 3D printing. This study used different fibre compositions (20,25,30) % mixed with polypropylene set at 190 ˚C temperature, 45 rpm speed, and 25 minutes. The material was left to cool to form clot to go through for the rheology process, and injection analysis was performed using Autodesk Moldflow Insight 2014. This study showed that a mixing temperature of 190 ˚C was suitable for forming a high shear mechanism. Kenaf fibre was treated in an alkaline solution of NaOH to 3 hours to prevent damage to the surface of the filler fibre in composites. Kenaf fibre at 6% of NaOH solution reaches a higher value for mechanical strength and roughness, resulting in better mechanical interlocking between the fibres and the matrix. In addition, analysis from Autodesk Moldflow Insight 2014 reveals that at 200 ˚C injection temperature pretend, the shear rate is higher creating smoother melt flow characteristics.